Evaluating the Nexus Between Exports, Imports, GDP, and Gross Capital Formation in South Africa - Ahmed Oluwatobi Adekunle (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This study evaluates the connection between exports, imports, GDP, and gross capital formation in South Africa.Method: The study employed the AutoRegressive Distributed Lag (ARDL) method, along with unit root tests to validate data stationarity, and bounds testing to confirm long-run cointegration among the variables. EViews 12 software was used to analyze the data spanning from 1986 to 2022.Results: The findings indicate a statistically significant positive relationship between imports and gross capital formation at the 1% level, suggesting that imports stimulate gross capital formation in South Africa. Exports also demonstrate a direct connection with gross capital formation. Empirically, both exports and imports are significant factors in enhancing the level of gross capital formation in the country. This indicates that increasing the gross domestic product (GDP) is crucial for diversifying exports, with economic policy being a major determinant that can promote investment in gross capital formation to boost both exports and imports. This sets the foundation for ensuring that exports and imports have a long-term impact on gross capital formation (GrCaF).Practical Implications for Economic Growth and Development: This study contributes to economic growth and development by highlighting the critical role of imports and exports in enhancing gross capital formation, which in turn improves the South African economy. The findings suggest that robust policies should be implemented, including tax cuts, increased infrastructure development, the promotion of manufactured goods, and advancements in domestic technologies. The government must provide stronger support for domestic industries to translate these efforts into economic growth and development.